Recent Advances in Sugarcane Genomics, Physiology, and Phenomics for Superior Agronomic Traits - Meena, Mintu Ram; Appunu, Chinnaswamy; Arun Kumar, R.; Manimekalai, R.; Vasantha, S.; Krishnappa, Gopalareddy; Kumar, Ravinder; Pandey, S. K.; Hemaprabha, G. (Frontiers in Genetics, 2022)
Advances in sugarcane breeding have contributed significantly to improvements in agronomic traits and crop yield. However, the growing global demand for sugar and biofuel in the context of climate change requires further improvements in cane and sugar yields. Attempts to achieve desired rates of genetic gain in sugarcane by conventional breeding means are difficult as many agronomic traits are genetically complex and polygenic with each gene exerting small effects. Unlike those of many other crops, the sugarcane genome is highly heterozygous due to its autopolyploid nature which further hinders the development of a comprehensive genetic map. Despite these limitations, many superior agronomic traits/genes for higher cane yield, sugar production, and disease/pest resistance have been identified by mapping of quantitative trait loci, genome-wide association studies, and transcriptome approaches. Improvements in traits controlled by one or two loci are relatively easy to achieve; however, this is not the case for traits governed by many genes. Many desirable phenotypic traits are controlled by quantitative trait nucleotides (QTNs) with small and variable effects. Assembling these desired QTNs by conventional breeding methods is time consuming and inefficient due to genetic drift. However, recent developments in genomics selection (GS) has allowed sugarcane researchers to select and accumulate desirable alleles imparting superior traits as GS is based on genome estimated breeding value (GEBV), which substantially increases the selection efficiency and genetic gain in sugarcane breeding programs. Next generation sequencing techniques coupled with genome editing technologies have provided new vistas in harnessing the sugarcane genome to look for desirable agronomic traits like erect canopy, leaf angle, prolonged greening, high biomass, deep root system, and non-flowering nature of the crop. Many desirable cane-yielding traits such as single cane weight, numbers of tillers, numbers of millable canes; and cane quality traits such as sucrose and sugar yield have been explored with these recent biotechnological tools. This review will focus on the recent advances in sugarcane genomics related to genetic gain and identification of favorable alleles for superior agronomic traits for further utilization in sugarcane breeding programs.